2014
DOI: 10.1142/9789814520652_0022
|View full text |Cite
|
Sign up to set email alerts
|

Nanopreparations for Oral Administration

Abstract: Oral delivery has distinct advantages over parenteral administration. These include ease of administration and improved patient compliance. Physiological barriers to oral drug delivery include low pH environment of the stomach, high enzymatic activity of the small intestine, and poor permeability of large molecular weight and hydrophilic compounds across the gastrointestinal epithelial layer. These barriers reduce stability and absorption of drug molecules to the systemic circulation. In order to overcome thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 206 publications
0
4
0
Order By: Relevance
“…The 10 mM concentrations, however, did not significantly enhance the mannitol permeability in jejunal segments. Colonic epithelium has been noted for the increased sensitivity to penetration enhancement and this may be the rationale for these results in the presence of PAMAM dendrimers . Factors that may contribute to this enhanced sensitivity may be the heightened ability of colonic tissue to absorb water and electrolytes, which may drag dendrimers into close proximity with epithelial layers and modulate tight junction opening and enhanced mannitol transport.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The 10 mM concentrations, however, did not significantly enhance the mannitol permeability in jejunal segments. Colonic epithelium has been noted for the increased sensitivity to penetration enhancement and this may be the rationale for these results in the presence of PAMAM dendrimers . Factors that may contribute to this enhanced sensitivity may be the heightened ability of colonic tissue to absorb water and electrolytes, which may drag dendrimers into close proximity with epithelial layers and modulate tight junction opening and enhanced mannitol transport.…”
Section: Discussionmentioning
confidence: 97%
“…The permeability of PAMAM dendrimers across intestinal epithelial barrier models has been evaluated in Caco-2 monolayers, ,, isolated rat intestinal tissue, , in vivo to rats and mice, , and in isolated human tissues as reported here. Of note was the permeability of PAMAM dendrimers ranging from 2.1 × 10 –6 for G3.5 probes in isolated human jejunum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decreased cytocompatibility for both groups was identified since we found that at Day 7, Dermabond and TMC3 had lower DNA concentrations than cells grown on plastic. The toxicity of Dermabond is likely due to cyanoacrylate degradation into cyanoacetate and formaldahyde via the inverse Knoevenagel reaction, but could be due to other metabolic pathways (Hubbard et al , 2014). The reduction of DNA content of cells grown on TMC3 may be due to the buildup of carbonic acid resulting from the release of carbon dioxide after reaction with water (Six and Richter, 2000), or may be due to decreased adhesion.…”
Section: Discussionmentioning
confidence: 99%